Alcohol consumption and kidney function decline in the elderly: alcohol and kidney disease. - Menon, Vandana; Katz, Ronit; Mukamal, Kenneth; Kestenbaum, Bryan; de Boer, Ian H; Siscovick, David S; Sarnak, Mark J; Shlipak, Michael G (Nephrol Dial Transplant, 2010)
BACKGROUND: Alcohol consumption appears to be protective for cardiovascular disease; however, its relationship with kidney disease is unclear. METHODS: This prospective cohort study included 4343 subjects from the Cardiovascular Health Study, a longitudinal, community-based cohort of persons aged ≥65 from four US communities. We used previously defined categories based on weekly alcohol consumption: none, former, <1 drink, 1-6 drinks, 7-13 drinks and ≥14 drinks. Cystatin C was measured at baseline, year 3 and year 7; eligible subjects had at least two measures. Estimated GFR(cys) was calculated from cystatin C. The primary outcome was rapid kidney function as an annual estimated GFR (eGFR(cys)) loss >3 mL/min/1.73 m(2)/year. RESULTS: Eight percent of the cohort reported former alcohol use and 52% reported current alcohol consumption. During a mean follow-up of 5.6 years, 1075 (25%) participants had rapid kidney function decline. In adjusted logistic regression models, there was no association between alcohol use and kidney function decline (odds ratio, 95% confidence interval: none = reference; former = 1.18, 0.89-1.56; <1 drink = 1.20, 0.99-1.47; 1-6 = 1.18, 0.95-1.45; 7-13 = 1.10, 0.80-1.53; >14 = 0.89, 0.61-1.13). Results were similar with kidney function decline as a continuous outcome. CONCLUSIONS: Our results suggest that moderate alcohol consumption has neither adverse nor beneficial effects on kidney function. Although clinicians will need to consider the potential deleterious effects associated with alcohol consumption, there does not appear to be a basis for recommending that older adults discontinue or initiate light to moderate alcohol consumption to protect against kidney disease.
Keywords: Aged; Aging; Alcohol Drinking; Cohort Studies; Cystatin C; Female; Glomerular Filtration Rate; Humans; Kidney; Kidney Diseases; Male; Prospective Studies

Diabetes and coronary heart disease as risk factors for mortality in older adults. - Carnethon, Mercedes R; Biggs, Mary L; Barzilay, Joshua; Kuller, Lewis H; Mozaffarian, Dariush; Mukamal, Kenneth; Smith, Nicholas L; Siscovick, David (Am J Med, 2010)
BACKGROUND: Type 2 diabetes has been described as a coronary heart disease (CHD) "risk equivalent." We tested whether cardiovascular and all-cause mortality rates were similar between participants with prevalent CHD vs diabetes in an older adult population in whom both glucose disorders and preexisting atherosclerosis are common. METHODS: The Cardiovascular Health Study is a longitudinal study of men and women (n=5784) aged > or =65 years at baseline who were followed from baseline (1989/1992-1993) through 2005 for mortality. Diabetes was defined by fasting plasma glucose > or =7.0 mmol/L or use of diabetes control medications. Prevalent CHD was determined by confirmed history of myocardial infarction, angina, or coronary revascularization. RESULTS: Following multivariable adjustment for other cardiovascular disease risk factors and subclinical atherosclerosis, CHD mortality risk was similar between participants with CHD alone vs diabetes alone (hazard ratio [HR] 1.04, 95% confidence interval [CI], 0.83-1.30). The proportion of mortality attributable to prevalent diabetes (population-attributable risk percent=8.4%) and prevalent CHD (6.7%) was similar in women, but the proportion of mortality attributable to CHD (16.5%) as compared with diabetes (6.4%) was markedly higher in men. Patterns were similar for cardiovascular disease mortality. By contrast, the adjusted relative hazard of total mortality was lower among participants with CHD alone (HR 0.85, 95% CI, 0.75-0.96) as compared with those who had diabetes alone. CONCLUSIONS: Among older adults, diabetes alone confers a risk for cardiovascular mortality similar to that from established clinical CHD. The public health burden of both diabetes and CHD is substantial, particularly among women.
Keywords: Aged; Coronary Disease; Diabetes Mellitus, Type 2; Female; Follow-Up Studies; Humans; Male; Prevalence; Risk Factors; Sex Distribution; Survival Rate; Time Factors; United States

Interactions of dietary whole-grain intake with fasting glucose- and insulin-related genetic loci in individuals of European descent: a meta-analysis of 14 cohort studies. - Nettleton, Jennifer A; McKeown, Nicola M; Kanoni, Stavroula; Lemaitre, Rozenn N; Hivert, Marie-France; Ngwa, Julius; van Rooij, Frank J A; Sonestedt, Emily; Wojczynski, Mary K; Ye, Zheng; Tanaka, Tosh; Garcia, Melissa; et al. (Diabetes Care, 2010)
OBJECTIVE: Whole-grain foods are touted for multiple health benefits, including enhancing insulin sensitivity and reducing type 2 diabetes risk. Recent genome-wide association studies (GWAS) have identified several single nucleotide polymorphisms (SNPs) associated with fasting glucose and insulin concentrations in individuals free of diabetes. We tested the hypothesis that whole-grain food intake and genetic variation interact to influence concentrations of fasting glucose and insulin. RESEARCH DESIGN AND METHODS: Via meta-analysis of data from 14 cohorts comprising ∼ 48,000 participants of European descent, we studied interactions of whole-grain intake with loci previously associated in GWAS with fasting glucose (16 loci) and/or insulin (2 loci) concentrations. For tests of interaction, we considered a P value <0.0028 (0.05 of 18 tests) as statistically significant. RESULTS: Greater whole-grain food intake was associated with lower fasting glucose and insulin concentrations independent of demographics, other dietary and lifestyle factors, and BMI (β [95% CI] per 1-serving-greater whole-grain intake: -0.009 mmol/l glucose [-0.013 to -0.005], P < 0.0001 and -0.011 pmol/l [ln] insulin [-0.015 to -0.007], P = 0.0003). No interactions met our multiple testing-adjusted statistical significance threshold. The strongest SNP interaction with whole-grain intake was rs780094 (GCKR) for fasting insulin (P = 0.006), where greater whole-grain intake was associated with a smaller reduction in fasting insulin concentrations in those with the insulin-raising allele. CONCLUSIONS: Our results support the favorable association of whole-grain intake with fasting glucose and insulin and suggest a potential interaction between variation in GCKR and whole-grain intake in influencing fasting insulin concentrations.
Keywords: Adult; Aged; Blood Glucose; Edible Grain; European Continental Ancestry Group; Fasting; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide

Hypertension, white matter hyperintensities, and concurrent impairments in mobility, cognition, and mood: the Cardiovascular Health Study. - Hajjar, Ihab; Quach, Lien; Yang, Frances; Chaves, Paulo H M; Newman, Anne B; Mukamal, Kenneth; Longstreth, Will; Inzitari, Marco; Lipsitz, Lewis A (Circulation, 2011)
BACKGROUND: Our objective was to investigate the association between hypertension and concurrent impairments in mobility, cognition, and mood; the role of brain white matter hyperintensities in mediating this association; and the impact of these impairments on disability and mortality in elderly hypertensive individuals. METHODS AND RESULTS: -Blood pressure, gait speed, digit symbol substitution test, and the Center for Epidemiological Studies Depression Scale were measured yearly (1992-1999) on 4700 participants in the Cardiovascular Health Study (age: 74.7, 58% women, 17% blacks, 68% hypertension, 3600 had brain magnetic resonance imaging in 1992-1993, survival data 1992-2005). Using latent profile analysis at baseline, we found that 498 (11%) subjects had concurrent impairments and 3086 (66%) were intact on all 3 measures. Between 1992 and 1999, 651 (21%) became impaired in all 3 domains. Hypertensive individuals were more likely to be impaired at baseline (odds ratio 1.23, 95% confidence interval 1.04 to 1.42, P=0.01) and become impaired during the follow-up (hazard ratio=1.3, 95% confidence interval 1.02 to 1.66, P=0.037). A greater degree of white matter hyperintensities was associated with impairments in the 3 domains (P=0.007) and mediated the association with hypertension (P=0.19 for hypertension after adjusting for white matter hyperintensities in the model, 21% hazard ratio change). Impairments in the 3 domains increased subsequent disability with hypertension (P<0.0001). Hypertension mortality also was increased in those impaired (compared with unimpaired hypertensive individuals: HR=1.10, 95% confidence interval 1.04 to 1.17, P=0.004). CONCLUSIONS: Hypertension increases the risk of concurrent impairments in mobility, cognition, and mood, which increases disability and mortality. This association is mediated in part by microvascular brain injury.
Keywords: Aged; Aged, 80 and over; Brain; Cognition Disorders; Female; Humans; Hypertension; Kaplan-Meier Estimate; Longitudinal Studies; Magnetic Resonance Imaging; Male; Microcirculation; Mobility Limitation; Mood Disorders; Nerve Fibers, Myelinated; Retrospective Studies; Risk Factors

Genetic variants associated with fasting glucose and insulin concentrations in an ethnically diverse population: results from the Population Architecture using Genomics and Epidemiology (PAGE) study. - Fesinmeyer, Megan D; Meigs, James B; North, Kari E; Schumacher, Fredrick R; Bůzková, Petra; Franceschini, Nora; Haessler, Jeffrey; Goodloe, Robert; Spencer, Kylee L; Voruganti, Venkata Saroja; Howard, Barbara V; Jackson, Rebecca; et al. (BMC Med Genet, 2013)
BACKGROUND: Multiple genome-wide association studies (GWAS) within European populations have implicated common genetic variants associated with insulin and glucose concentrations. In contrast, few studies have been conducted within minority groups, which carry the highest burden of impaired glucose homeostasis and type 2 diabetes in the U.S. METHODS: As part of the 'Population Architecture using Genomics and Epidemiology (PAGE) Consortium, we investigated the association of up to 10 GWAS-identified single nucleotide polymorphisms (SNPs) in 8 genetic regions with glucose or insulin concentrations in up to 36,579 non-diabetic subjects including 23,323 European Americans (EA) and 7,526 African Americans (AA), 3,140 Hispanics, 1,779 American Indians (AI), and 811 Asians. We estimated the association between each SNP and fasting glucose or log-transformed fasting insulin, followed by meta-analysis to combine results across PAGE sites. RESULTS: Overall, our results show that 9/9 GWAS SNPs are associated with glucose in EA (p = 0.04 to 9 × 10-15), versus 3/9 in AA (p= 0.03 to 6 × 10-5), 3/4 SNPs in Hispanics, 2/4 SNPs in AI, and 1/2 SNPs in Asians. For insulin we observed a significant association with rs780094/GCKR in EA, Hispanics and AI only. CONCLUSIONS: Generalization of results across multiple racial/ethnic groups helps confirm the relevance of some of these loci for glucose and insulin metabolism. Lack of association in non-EA groups may be due to insufficient power, or to unique patterns of linkage disequilibrium.
Keywords: Adaptor Proteins, Signal Transducing; Adult; African Americans; Aged; Alleles; Asian Continental Ancestry Group; Blood Glucose; Diabetes Mellitus, Type 2; European Continental Ancestry Group; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Genomics; Hispanic Americans; Humans; Indians, North American; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Transcription Factor 7-Like 2 Protein

Higher magnesium intake is associated with lower fasting glucose and insulin, with no evidence of interaction with select genetic loci, in a meta-analysis of 15 CHARGE Consortium Studies. - Hruby, Adela; Ngwa, Julius S; Renstrom, Frida; Wojczynski, Mary K; Ganna, Andrea; Hallmans, Göran; Houston, Denise K; Jacques, Paul F; Kanoni, Stavroula; Lehtimäki, Terho; Lemaitre, Rozenn N; Manichaikul, Ani; et al. (J Nutr, 2013)
Favorable associations between magnesium intake and glycemic traits, such as fasting glucose and insulin, are observed in observational and clinical studies, but whether genetic variation affects these associations is largely unknown. We hypothesized that single nucleotide polymorphisms (SNPs) associated with either glycemic traits or magnesium metabolism affect the association between magnesium intake and fasting glucose and insulin. Fifteen studies from the CHARGE (Cohorts for Heart and Aging Research in Genomic Epidemiology) Consortium provided data from up to 52,684 participants of European descent without known diabetes. In fixed-effects meta-analyses, we quantified 1) cross-sectional associations of dietary magnesium intake with fasting glucose (mmol/L) and insulin (ln-pmol/L) and 2) interactions between magnesium intake and SNPs related to fasting glucose (16 SNPs), insulin (2 SNPs), or magnesium (8 SNPs) on fasting glucose and insulin. After adjustment for age, sex, energy intake, BMI, and behavioral risk factors, magnesium (per 50-mg/d increment) was inversely associated with fasting glucose [β = -0.009 mmol/L (95% CI: -0.013, -0.005), P < 0.0001] and insulin [-0.020 ln-pmol/L (95% CI: -0.024, -0.017), P < 0.0001]. No magnesium-related SNP or interaction between any SNP and magnesium reached significance after correction for multiple testing. However, rs2274924 in magnesium transporter-encoding TRPM6 showed a nominal association (uncorrected P = 0.03) with glucose, and rs11558471 in SLC30A8 and rs3740393 near CNNM2 showed a nominal interaction (uncorrected, both P = 0.02) with magnesium on glucose. Consistent with other studies, a higher magnesium intake was associated with lower fasting glucose and insulin. Nominal evidence of TRPM6 influence and magnesium interaction with select loci suggests that further investigation is warranted.
Keywords: Blood Glucose; Female; Genetic Loci; Humans; Insulin; Magnesium; Male; Polymorphism, Single Nucleotide; Trace Elements; TRPM Cation Channels

Insulin resistance and risk of incident heart failure: Cardiovascular Health Study. - Banerjee, Dipanjan; Biggs, Mary L; Mercer, Laina; Mukamal, Kenneth; Kaplan, Robert; Barzilay, Joshua; Kuller, Lewis; Kizer, Jorge R; Djoussé, Luc; Tracy, Russell; Zieman, Susan; Lloyd-Jones, Donald; et al. (Circ Heart Fail, 2013)
BACKGROUND: Patients with heart failure (HF) have higher fasting insulin levels and a higher prevalence of insulin resistance as compared with matched controls. Insulin resistance leads to structural abnormalities in the heart, such as increased left atrial size, left ventricular mass, and alterations in transmitral velocity that can precede the diagnosis of HF. It is not known whether insulin resistance precedes the development of HF or whether the relationship between insulin resistance and HF is present among adults with HF caused by nonischemic heart disease. METHODS AND RESULTS: We examined 4425 participants (60% women) from the Cardiovascular Health Study after excluding those with HF, myocardial infarction, or treated diabetes mellitus at baseline. We used Cox proportional hazards models to estimate the relative risk of incident HF associated with fasting insulin measured at study entry. There were 1216 cases of incident HF (1103 without antecedent myocardial infarction) during a median follow-up of 12 years (maximum, 19 years). Fasting insulin levels were positively associated with the risk of incident HF (hazard ratio, 1.10; 95% confidence interval, 1.05-1.15, per SD change) when adjusted for age, sex, race, field center, physical activity, smoking, alcohol intake, high-density lipoprotein-cholesterol, total cholesterol, systolic blood pressure, and waist circumference. The association between fasting insulin levels and incident HF was similar for HF without antecedent myocardial infarction (hazard ratio, 1.10; 95% confidence interval, 1.05-1.15). Measures of left atrial size, left ventricular mass, and peak A velocity at baseline were associated both with fasting insulin levels and with HF; however, additional statistical adjustment for these parameters did not completely attenuate the insulin-HF estimate (hazard ratio, 1.08; 95% confidence interval, 1.03-1.14 per 1-SD increase in fasting insulin). CONCLUSIONS: Fasting insulin was positively associated with adverse echocardiographic features and risk of subsequent HF in Cardiovascular Health Study participants, including those without an antecedent myocardial infarction. CLINICAL TRIAL REGISTRATION: URL: http://www.clinicaltrials.gov. Unique identifier: NCT00005133.
Keywords: Aged; Female; Heart Atria; Heart Failure; Heart Ventricles; Humans; Incidence; Insulin; Insulin Resistance; Male; Middle Aged; Myocardial Infarction; Organ Size; Proportional Hazards Models; Prospective Studies

Obesity is associated with a lower resting oxygen saturation in the ambulatory elderly: results from the cardiovascular health study. - Kapur, Vishesh K; Wilsdon, Anthony G; Au, David; Avdalovic, Mark; Enright, Paul; Fan, Vincent S; Hansel, Nadia N; Heckbert, Susan R; Jiang, Rui; Krishnan, Jerry A; Mukamal, Kenneth; Yende, Sachin; et al. (Respir Care, 2013)
BACKGROUND: The contribution of obesity to hypoxemia has not been reported in a community-based study. Our hypothesis was that increasing obesity would be independently associated with lower SpO2 in an ambulatory elderly population. METHODS: The Cardiovascular Health Study ascertained resting SpO2 in 2,252 subjects over age 64. We used multiple linear regression to estimate the association of body mass index (BMI) with SpO2 and to adjust for potentially confounding factors. Covariates including age, sex, race, smoking, airway obstruction (based on spirometry), self reported diagnosis of emphysema, asthma, heart failure, and left ventricular function (by echocardiography) were evaluated. RESULTS: Among 2,252 subjects the mean and median SpO2 were 97.6% and 98.0% respectively; 5% of subjects had SpO2 values below 95%. BMI was negatively correlated with SpO2 (Spearman R = -0.27, P < .001). The mean difference in SpO2 between the lowest and highest BMI categories (< 25 kg/m(2) and ≥ 35 kg/m(2)) was 1.33% (95% CI 0.89-1.78%). In multivariable linear regression analysis, SpO2 was significantly inversely associated with BMI (1.4% per 10 units of BMI, 95% CI 1.2-1.6, for whites/others, and 0.87% per 10 units of BMI, 95% CI 0.47-1.27, for African Americans). CONCLUSIONS: We found a narrow distribution of SpO2 values in a community-based sample of ambulatory elderly. Obesity was a strong independent contributor to a low SpO2, with effects comparable to or greater than other factors clinically associated with lower SpO2.
Keywords: African Americans; Age Factors; Aged; Aged, 80 and over; Body Mass Index; European Continental Ancestry Group; Female; Humans; Male; Obesity; Oximetry; Oxygen; Smoking; Waist Circumference

Association between alcohol and cardiovascular disease: Mendelian randomisation analysis based on individual participant data. - Holmes, Michael V; Dale, Caroline E; Zuccolo, Luisa; Silverwood, Richard J; Guo, Yiran; Ye, Zheng; Prieto-Merino, David; Dehghan, Abbas; Trompet, Stella; Wong, Andrew; Cavadino, Alana; Drogan, Dagmar; et al. (BMJ, 2014)
OBJECTIVE: To use the rs1229984 variant in the alcohol dehydrogenase 1B gene (ADH1B) as an instrument to investigate the causal role of alcohol in cardiovascular disease. DESIGN: Mendelian randomisation meta-analysis of 56 epidemiological studies. PARTICIPANTS: 261 991 individuals of European descent, including 20 259 coronary heart disease cases and 10 164 stroke events. Data were available on ADH1B rs1229984 variant, alcohol phenotypes, and cardiovascular biomarkers. MAIN OUTCOME MEASURES: Odds ratio for coronary heart disease and stroke associated with the ADH1B variant in all individuals and by categories of alcohol consumption. RESULTS: Carriers of the A-allele of ADH1B rs1229984 consumed 17.2% fewer units of alcohol per week (95% confidence interval 15.6% to 18.9%), had a lower prevalence of binge drinking (odds ratio 0.78 (95% CI 0.73 to 0.84)), and had higher abstention (odds ratio 1.27 (1.21 to 1.34)) than non-carriers. Rs1229984 A-allele carriers had lower systolic blood pressure (-0.88 (-1.19 to -0.56) mm Hg), interleukin-6 levels (-5.2% (-7.8 to -2.4%)), waist circumference (-0.3 (-0.6 to -0.1) cm), and body mass index (-0.17 (-0.24 to -0.10) kg/m(2)). Rs1229984 A-allele carriers had lower odds of coronary heart disease (odds ratio 0.90 (0.84 to 0.96)). The protective association of the ADH1B rs1229984 A-allele variant remained the same across all categories of alcohol consumption (P=0.83 for heterogeneity). Although no association of rs1229984 was identified with the combined subtypes of stroke, carriers of the A-allele had lower odds of ischaemic stroke (odds ratio 0.83 (0.72 to 0.95)). CONCLUSIONS: Individuals with a genetic variant associated with non-drinking and lower alcohol consumption had a more favourable cardiovascular profile and a reduced risk of coronary heart disease than those without the genetic variant. This suggests that reduction of alcohol consumption, even for light to moderate drinkers, is beneficial for cardiovascular health.
Keywords: Adult; Aged; Alcohol Dehydrogenase; Alcohol Drinking; Biomarkers; Coronary Disease; Female; Genetic Markers; Genotype; Humans; Male; Mendelian Randomization Analysis; Middle Aged; Models, Statistical; Polymorphism, Single Nucleotide; Stroke

Consumption of meat is associated with higher fasting glucose and insulin concentrations regardless of glucose and insulin genetic risk scores: a meta-analysis of 50,345 Caucasians. - Fretts, Amanda M; Follis, Jack L; Nettleton, Jennifer A; Lemaitre, Rozenn N; Ngwa, Julius S; Wojczynski, Mary K; Kalafati, Ioanna Panagiota; Varga, Tibor V; Frazier-Wood, Alexis C; Houston, Denise K; Lahti, Jari; Ericson, Ulrika; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Recent studies suggest that meat intake is associated with diabetes-related phenotypes. However, whether the associations of meat intake and glucose and insulin homeostasis are modified by genes related to glucose and insulin is unknown. OBJECTIVE: We investigated the associations of meat intake and the interaction of meat with genotype on fasting glucose and insulin concentrations in Caucasians free of diabetes mellitus. DESIGN: Fourteen studies that are part of the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium participated in the analysis. Data were provided for up to 50,345 participants. Using linear regression within studies and a fixed-effects meta-analysis across studies, we examined 1) the associations of processed meat and unprocessed red meat intake with fasting glucose and insulin concentrations; and 2) the interactions of processed meat and unprocessed red meat with genetic risk score related to fasting glucose or insulin resistance on fasting glucose and insulin concentrations. RESULTS: Processed meat was associated with higher fasting glucose, and unprocessed red meat was associated with both higher fasting glucose and fasting insulin concentrations after adjustment for potential confounders [not including body mass index (BMI)]. For every additional 50-g serving of processed meat per day, fasting glucose was 0.021 mmol/L (95% CI: 0.011, 0.030 mmol/L) higher. Every additional 100-g serving of unprocessed red meat per day was associated with a 0.037-mmol/L (95% CI: 0.023, 0.051-mmol/L) higher fasting glucose concentration and a 0.049-ln-pmol/L (95% CI: 0.035, 0.063-ln-pmol/L) higher fasting insulin concentration. After additional adjustment for BMI, observed associations were attenuated and no longer statistically significant. The association of processed meat and fasting insulin did not reach statistical significance after correction for multiple comparisons. Observed associations were not modified by genetic loci known to influence fasting glucose or insulin resistance. CONCLUSION: The association of higher fasting glucose and insulin concentrations with meat consumption was not modified by an index of glucose- and insulin-related single-nucleotide polymorphisms. Six of the participating studies are registered at clinicaltrials.gov as NCT0000513 (Atherosclerosis Risk in Communities), NCT00149435 (Cardiovascular Health Study), NCT00005136 (Family Heart Study), NCT00005121 (Framingham Heart Study), NCT00083369 (Genetics of Lipid Lowering Drugs and Diet Network), and NCT00005487 (Multi-Ethnic Study of Atherosclerosis).
Keywords: Blood Glucose; Cohort Studies; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hyperglycemia; Hyperinsulinism; Insulin; Insulin Resistance; Insulin-Secreting Cells; Meat; Meat Products; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Gene × dietary pattern interactions in obesity: analysis of up to 68 317 adults of European ancestry. - Nettleton, Jennifer A; Follis, Jack L; Ngwa, Julius S; Smith, Caren E; Ahmad, Shafqat; Tanaka, Toshiko; Wojczynski, Mary K; Voortman, Trudy; Lemaitre, Rozenn N; Kristiansson, Kati; Nuotio, Marja-Liisa; Houston, Denise K; et al. (Hum Mol Genet, 2015)
Obesity is highly heritable. Genetic variants showing robust associations with obesity traits have been identified through genome-wide association studies. We investigated whether a composite score representing healthy diet modifies associations of these variants with obesity traits. Totally, 32 body mass index (BMI)- and 14 waist-hip ratio (WHR)-associated single nucleotide polymorphisms were genotyped, and genetic risk scores (GRS) were calculated in 18 cohorts of European ancestry (n = 68 317). Diet score was calculated based on self-reported intakes of whole grains, fish, fruits, vegetables, nuts/seeds (favorable) and red/processed meats, sweets, sugar-sweetened beverages and fried potatoes (unfavorable). Multivariable adjusted, linear regression within each cohort followed by inverse variance-weighted, fixed-effects meta-analysis was used to characterize: (a) associations of each GRS with BMI and BMI-adjusted WHR and (b) diet score modification of genetic associations with BMI and BMI-adjusted WHR. Nominally significant interactions (P = 0.006-0.04) were observed between the diet score and WHR-GRS (but not BMI-GRS), two WHR loci (GRB14 rs10195252; LYPLAL1 rs4846567) and two BMI loci (LRRN6C rs10968576; MTIF3 rs4771122), for the respective BMI-adjusted WHR or BMI outcomes. Although the magnitudes of these select interactions were small, our data indicated that associations between genetic predisposition and obesity traits were stronger with a healthier diet. Our findings generate interesting hypotheses; however, experimental and functional studies are needed to determine their clinical relevance.
Keywords: Adult; Body Mass Index; Case-Control Studies; Diet, Western; Epistasis, Genetic; European Continental Ancestry Group; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Obesity; Polymorphism, Single Nucleotide

Plasma phospholipid very-long-chain saturated fatty acids and incident diabetes in older adults: the Cardiovascular Health Study. - Lemaitre, Rozenn N; Fretts, Amanda M; Sitlani, Colleen M; Biggs, Mary L; Mukamal, Kenneth; King, Irena B; Song, Xiaoling; Djoussé, Luc; Siscovick, David S; McKnight, Barbara; Sotoodehnia, Nona; Kizer, Jorge R; et al. (Am J Clin Nutr, 2015)
BACKGROUND: Circulating saturated fatty acids (SFAs) are integrated biomarkers of diet and metabolism that may influence the pathogenesis of diabetes. In epidemiologic studies, circulating levels of palmitic acid (16:0) are associated with diabetes; however, very-long-chain SFAs (VLSFAs), with 20 or more carbons, differ from palmitic acid in their biological activities, and little is known of the association of circulating VLSFA with diabetes. OBJECTIVE: By using data from the Cardiovascular Health Study, we examined the associations of plasma phospholipid VLSFA levels measured at baseline with subsequent incident diabetes. DESIGN: A total of 3179 older adults, with a mean age of 75 y at study baseline (1992-1993), were followed through 2011. We used multiple proportional hazards regression to examine the associations of arachidic acid (20:0), behenic acid (22:0), and lignoceric acid (24:0) with diabetes. RESULTS: Baseline levels of each VLSFA were cross-sectionally associated with lower triglyceride levels and lower circulating palmitic acid. We identified 284 incident diabetes cases during follow-up. Compared with the lowest quartile, levels of arachidic acid in the highest quartile of the fatty acid distribution were associated with a 47% lower risk of diabetes (95% CI: 23%, 63%; P-trend: <0.001), after adjustment for demographics, lifestyle factors, and clinical conditions. In analogous comparisons, levels of behenic and lignoceric acid were similarly associated with 33% (95% CI: 6%, 53%; P-trend: 0.02) and 37% (95% CI: 11%, 55%; P-trend: 0.01) lower diabetes risk, respectively. Adjustment for triglycerides and palmitic acid attenuated the associations toward the null, and only the association of arachidic acid remained statistically significant (32% lower risk for fourth vs. first quartile; P-trend: 0.04). CONCLUSIONS: These results suggest that circulating VLSFAs are associated with a lower risk of diabetes, and these associations may be mediated by lower triglycerides and palmitic acid. The study highlights the need to distinguish the effects of different SFAs and to explore determinants of circulating VLSFAs. This trial was registered at clinicaltrials.gov as NCT00005133.
Keywords: Aged; Aged, 80 and over; Biomarkers; Cross-Sectional Studies; Diabetes Mellitus; Diet; Eicosanoic Acids; Fatty Acids; Fatty Acids, Nonesterified; Female; Follow-Up Studies; Humans; Incidence; Male; Observational Studies as Topic; Palmitic Acid; Phospholipids; Prospective Studies; Risk Factors; Triglycerides

Urine Collagen Fragments and CKD Progression-The Cardiovascular Health Study. - Ix, Joachim H; Biggs, Mary L; Mukamal, Kenneth; Djoussé, Luc; Siscovick, David; Tracy, Russell; Katz, Ronit; Delaney, Joseph A; Chaves, Paulo; Rifkin, Dena E; Hughes-Austin, Jan M; Garimella, Pranav S; et al. (J Am Soc Nephrol, 2015)
Tubulointerstitial fibrosis is common with ageing and strongly prognostic for ESRD but is poorly captured by eGFR or urine albumin to creatinine ratio (ACR). Higher urine levels of procollagen type III N-terminal propeptide (PIIINP) mark the severity of tubulointerstitial fibrosis in biopsy studies, but the association of urine PIIINP with CKD progression is unknown. Among community-living persons aged ≥65 years, we measured PIIINP in spot urine specimens from the 1996 to 1997 Cardiovascular Health Study visit among individuals with CKD progression (30% decline in eGFR over 9 years, n=192) or incident ESRD (n=54) during follow-up, and in 958 randomly selected participants. We evaluated associations of urine PIIINP with CKD progression and incident ESRD. Associations of urine PIIINP with cardiovascular disease, heart failure, and death were evaluated as secondary end points. At baseline, mean age (±SD) was 78±5 years, mean eGFR was 63±18 ml/min per 1.73 m(2), and median urine PIIINP was 2.6 (interquartile range, 1.4-4.2) μg/L. In a case-control study (192 participants, 231 controls), each doubling of urine PIIINP associated with 22% higher odds of CKD progression (adjusted odds ratio, 1.22; 95% confidence interval, 1.00 to 1.49). Higher urine PIIINP level was also associated with incident ESRD, but results were not significant in fully adjusted models. In a prospective study among the 958 randomly selected participants, higher urine PIIINP was significantly associated with death, but not with incident cardiovascular disease or heart failure. These data suggest higher urine PIIINP levels associate with CKD progression independently of eGFR and ACR in older individuals.
Keywords: Aged; Cardiovascular Diseases; Case-Control Studies; Disease Progression; Female; Heart Failure; Humans; Kidney Failure, Chronic; Male; Peptide Fragments; Procollagen; Prospective Studies; Renal Insufficiency, Chronic

KLB is associated with alcohol drinking, and its gene product β-Klotho is necessary for FGF21 regulation of alcohol preference. - Schumann, Gunter; Liu, Chunyu; O'Reilly, Paul; Gao, He; Song, Parkyong; Xu, Bing; Ruggeri, Barbara; Amin, Najaf; Jia, Tianye; Preis, Sarah; Segura Lepe, Marcelo; Akira, Shizuo; et al. (Proc Natl Acad Sci U S A, 2016)
Excessive alcohol consumption is a major public health problem worldwide. Although drinking habits are known to be inherited, few genes have been identified that are robustly linked to alcohol drinking. We conducted a genome-wide association metaanalysis and replication study among >105,000 individuals of European ancestry and identified β-Klotho (KLB) as a locus associated with alcohol consumption (rs11940694; P = 9.2 × 10(-12)). β-Klotho is an obligate coreceptor for the hormone FGF21, which is secreted from the liver and implicated in macronutrient preference in humans. We show that brain-specific β-Klotho KO mice have an increased alcohol preference and that FGF21 inhibits alcohol drinking by acting on the brain. These data suggest that a liver-brain endocrine axis may play an important role in the regulation of alcohol drinking behavior and provide a unique pharmacologic target for reducing alcohol consumption.

The Association Between IGF-I and IGFBP-3 and Incident Diabetes in an Older Population of Men and Women in the Cardiovascular Health Study. - Aneke-Nash, Chino S; Xue, XiaoNan; Qi, Qibin; Biggs, Mary L; Cappola, Anne; Kuller, Lewis; Pollak, Michael; Psaty, Bruce M; Siscovick, David; Mukamal, Kenneth; Strickler, Howard D; Kaplan, Robert C (J Clin Endocrinol Metab, 2017)
Context: Insulin-like growth factor-I (IGF-I) has structural and functional similarities to insulin and may play a role in glucose homeostasis, along with insulin-like growth factor binding protein-3 (IGFBP-3), which binds the majority of circulating IGF-I. Objective: To assess whether IGF-I and IGFBP-3 are associated with a higher risk of incident diabetes in older adults. Design: Participants in the Cardiovascular Health Study (n = 3133), a cohort of adults aged ≥65 years, were observed for 16 years (n = 3133) for the development of incident diabetes. Statistical models were fit separately for men and women because of interactions with sex (P interaction: IGF-I, 0.02; IGFBP-3, 0.009) and were adjusted for relevant covariates. Setting: General community. Participants: Older adults who were nondiabetic at baseline and who did not develop diabetes within the first year of follow-up. Interventions: Not applicable. Main Outcome Measure: Incident diabetes as measured by fasting plasma glucose (FPG) ≥126 mg/dL, non-FPG ≥200 mg/dL, use of pharmacological treatment of diabetes, or existence of two or more inpatient or three or more outpatient or (at least one inpatient and at least one outpatient) Centers for Medicare & Medicaid Services claims with the diagnostic International Classification of Diseases, Ninth Revision, Clinical Modification code of 250.xx. Results: In women, higher IGFBP-3 (hazard ratio tertile 3 vs tertile 1 = 2.30; 95% confidence interval, 1.55 to 3.40; P trend < 0.0001) was significantly associated with incident diabetes. Total IGF-I was not significantly associated with incident diabetes. In men, neither IGF-I nor IGFBP-3 was significantly associated with incident diabetes. Conclusions: We confirmed a previously reported association between circulating IGFBP-3 and diabetes risk in the older adult population, establishing that this association is present among women but could not be shown to be associated in men.
Keywords: Aged; Aged, 80 and over; Biomarkers; Blood Glucose; Cardiovascular Diseases; Cohort Studies; Diabetes Mellitus; Female; Humans; Incidence; Insulin-Like Growth Factor Binding Protein 3; Insulin-Like Growth Factor I; Longitudinal Studies; Male; New England; Prospective Studies; Risk

Sleep-disordered breathing is associated with higher carboxymethyllysine level in elderly women but not elderly men in the cardiovascular health study. - Ahiawodzi, Peter D; Kerber, Richard A; Taylor, Kira C; Groves, Frank D; O'Brien, Elizabeth; Ix, Joachim H; Kizer, Jorge R; Djoussé, Luc; Tracy, Russell P; Newman, Anne B; Siscovick, David S; Robbins, John; et al. (Biomarkers, 2017)
CONTEXT: Carboxymethyl-lysine (CML) results from oxidative stress and has been linked to cardiovascular disease. OBJECTIVE: The objective of this study is to investigate the association between sleep-disordered breathing (SDB) - a source of oxidative stress - and CML. MATERIALS AND METHODS: About 1002 participants in the Cardiovascular Health Study (CHS) were studied. RESULTS: Women with SDB had significantly higher CML concentration compared with those without SDB (OR = 1.63, 95%CI = 1.03-2.58, p = 0.04). The association was not significant among men. DISCUSSION: SDB was associated with CML concentration among elderly women but not men in the Cardiovascular Health Study. CONCLUSION: Accumulation of CML may be an adverse health consequence of SDB.

The Impact of Time Horizon on Classification Accuracy: Application of Machine Learning to Prediction of Incident Coronary Heart Disease. - Simon, Steven; Mandair, Divneet; Albakri, Abdel; Fohner, Alison; Simon, Noah; Lange, Leslie; Biggs, Mary; Mukamal, Kenneth; Psaty, Bruce; Rosenberg, Michael (JMIR Cardio, 2022)
BACKGROUND: Many machine learning approaches are limited to classification of outcomes rather than longitudinal prediction. One strategy to use machine learning in clinical risk prediction is to classify outcomes over a given time horizon. However, it is not well-known how to identify the optimal time horizon for risk prediction. OBJECTIVE: In this study, we aim to identify an optimal time horizon for classification of incident myocardial infarction (MI) using machine learning approaches looped over outcomes with increasing time horizons. Additionally, we sought to compare the performance of these models with the traditional Framingham Heart Study (FHS) coronary heart disease gender-specific Cox proportional hazards regression model. METHODS: We analyzed data from a single clinic visit of 5201 participants of a cardiovascular health study. We examined 61 variables collected from this baseline exam, including demographic and biologic data, medical history, medications, serum biomarkers, electrocardiographic, and echocardiographic data. We compared several machine learning methods (eg, random forest, L1 regression, gradient boosted decision tree, support vector machine, and k-nearest neighbor) trained to predict incident MI that occurred within time horizons ranging from 500-10,000 days of follow-up. Models were compared on a 20% held-out testing set using area under the receiver operating characteristic curve (AUROC). Variable importance was performed for random forest and L1 regression models across time points. We compared results with the FHS coronary heart disease gender-specific Cox proportional hazards regression functions. RESULTS: There were 4190 participants included in the analysis, with 2522 (60.2%) female participants and an average age of 72.6 years. Over 10,000 days of follow-up, there were 813 incident MI events. The machine learning models were most predictive over moderate follow-up time horizons (ie, 1500-2500 days). Overall, the L1 (Lasso) logistic regression demonstrated the strongest classification accuracy across all time horizons. This model was most predictive at 1500 days follow-up, with an AUROC of 0.71. The most influential variables differed by follow-up time and model, with gender being the most important feature for the L1 regression and weight for the random forest model across all time frames. Compared with the Framingham Cox function, the L1 and random forest models performed better across all time frames beyond 1500 days. CONCLUSIONS: In a population free of coronary heart disease, machine learning techniques can be used to predict incident MI at varying time horizons with reasonable accuracy, with the strongest prediction accuracy in moderate follow-up periods. Validation across additional populations is needed to confirm the validity of this approach in risk prediction.

Multiple Prior Live Births are Associated with Cardiac Remodeling and Heart Failure Risk in Women. - Sarma, Amy A; Paniagua, Samantha M; Lau, Emily S; Wang, Dongyu; Liu, Elizabeth E; Larson, Martin G; Hamburg, Naomi M; Mitchell, Gary F; Kizer, Jorge; Psaty, Bruce M; Allen, Norrina B; Lely, A Titia; et al. (J Card Fail, 2023)
INTRODUCTION: Greater parity has been associated with cardiovascular disease risk, though effects on cardiac remodeling and heart failure risk remain unclear. METHODS: We examined the association of number of live births and echocardiographic measures of cardiac structure and function in participants of the Framingham Heart Study (FHS) using multivariable linear regression. We next examined the association of parity with incident heart failure with preserved (HFpEF) or reduced (HFrEF) ejection fraction using a Fine-Gray subdistribution hazards model in a pooled analysis of n=12,635 participants of FHS, the Cardiovascular Health Study, the Multi-Ethnic Study of Atherosclerosis, and Prevention of Renal and Vascular Endstage Disease. Secondary analyses included major CVD, MI, and stroke. RESULTS: Among n=3931 FHS participants (mean age 48 ± 13 years), higher number of live births was associated with worse LV fractional shortening (multivariable β -1.11 (0.31), p= 0.0005 in ≥ 5 live births vs nulliparous women) and worse cardiac mechanics including global circumferential strain and longitudinal and radial dyssynchrony (p< 0.01 for all comparing ≥ 5 live births vs nulliparity). When examining HF subtypes, women with ≥5 live births were at higher risk of developing future HFrEF compared with nulliparous women (HR 1.93, 95% CI 1.19-3.12, p=0.008); by contrast, a lower risk of HFpEF was observed (HR 0.58, 95% CI 0.37-0.91, p=0.02). CONCLUSIONS: Greater number of live births are associated with worse cardiac structure and function. While there was no association with overall HF, a higher number of live births was associated with greater risk for incident HFrEF.